The atomic packing structure of Al-(TM)-Y metallic glasses. (August 2019) - Xiong, X.Z.; Yi, J.J.; Kong, L.T.; Jiang, Z.; Huang, Y.Y.; Li, J.F.
Abstract: The atomic packing structure of Al90.5 Y9.5, Al89.5 Fe4.5 Y6, Al85.5 Ni9.5 Y5, Al89 Co5.5 Y5.5 and Al85.5 Co9.5 Y5 metallic glasses (MGs) was studied using the extended X-ray absorption fine structure (EXAFS) technique, and the atomic packing efficiency (APE) of solute-centered clusters was calculated. The results indicated that both Co- and Y-centered clusters possess higher APE in Al89 Co5.5 Y5.5 MG than in Al85.5 Co9.5 Y5 MG, due to which the former has the best glass-forming ability (GFA) in Al–Co–Y system. The chemical property of transition metals (TMs) influences the medium range ordering, i.e. the connection of solute-centered clusters. As TM element changes from Fe, Co to Ni, the TM-centered clusters tend to share more and more Al atoms, resulting in the sequential increase of the concentration ratio of TM/Y in Al89.5 Fe4.5 Y6, Al89 Co5.5 Y5.5 and Al85.5 Ni9.5 Y5 MGs that have the best GFA in their respective alloy system. Highlights: EXAFS of several Al–Y, Al-TM-Y (TM = Fe, Ni, Co) metallic glasses are measured. Coordination numbers of Al around TM and Y atoms and interatomic distance were determined. Atomic packing efficiency of solute-centered clusters was evaluated. The way for TM-centered clusters to connect depends on the type of TM. Difference in glass-forming ability was analyzed.